2002
DOI: 10.1523/jneurosci.22-05-01679.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intracellular Cholesterol Transport Alters Presenilin Localization and Amyloid Precursor Protein Processing in Neuronal Cells

Abstract: Generation of amyloid-beta (Abeta) from the amyloid precursor protein (APP) requires proteolytic cleavage by two proteases, beta- and gamma-secretase. Several lines of evidence suggest a role for cholesterol on secretase activities, although the responsible cellular mechanisms remain unclear. Here we show that alterations in cholesterol transport from late endocytic organelles to the endoplasmic reticulum have important consequences for both APP processing and the localization of gamma-secretase-associated pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
194
3
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(218 citation statements)
references
References 49 publications
18
194
3
3
Order By: Relevance
“…However, cholesterol accumulates in late endosome-like storage organelles when intracellular cholesterol transport is inhibited. Interestingly, PS1 and PS2 also redistribute to these organelles and consequently result in enhanced ␥-secretase processing of APP (35). In agreement with these data, we show that components of the ␥-secretase complex reside in cholesterol-rich domains of TGN and TGN-derived vesicles (containing syntaxin 6 and VAMP4), and recycling endosomes (containing syntaxin 13) and are not readily detectable in plasma membrane rafts (containing SNAP-23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, cholesterol accumulates in late endosome-like storage organelles when intracellular cholesterol transport is inhibited. Interestingly, PS1 and PS2 also redistribute to these organelles and consequently result in enhanced ␥-secretase processing of APP (35). In agreement with these data, we show that components of the ␥-secretase complex reside in cholesterol-rich domains of TGN and TGN-derived vesicles (containing syntaxin 6 and VAMP4), and recycling endosomes (containing syntaxin 13) and are not readily detectable in plasma membrane rafts (containing SNAP-23).…”
Section: Discussionsupporting
confidence: 88%
“…First, DIMs were found to be the principal compartment containing monomeric and oligomeric A␤ in brain (30,31). Second, experimental manipulations that result in cholesterol loading and depletion, or affect intracellular cholesterol transport, modulate A␤ production in cultured cells and animal models (26,(32)(33)(34)(35). Third, BACE1 is localized and cleaves APP in lipid rafts (33,36).…”
mentioning
confidence: 99%
“…The average age of patients was 79.8 Ϯ 2.0 (range 54-94). Average postmortem interval for all AD patients was 5.6 Ϯ 0.6 h (range [2][3][4][5][6][7][8][9][10][11][12][13][14]. No clinical stage-associated difference in average postmortem interval was present.…”
Section: Methodsmentioning
confidence: 99%
“…Two factors that are believed to contribute to neuronal dysfunction and degeneration in AD are increased oxidative stress and increased production of neurotoxic forms of A␤ (2). Alterations in lipid metabolism may also play roles in AD because the risk of AD is affected by inheritance of different isoforms of apolipoprotein E (3), changes in cholesterol metabolism can affect A␤ production in cell culture and in vivo (4)(5)(6), and drugs that lower cholesterol levels may reduce the risk of AD (7,8). However, a direct link between alterations in the metabolism of cholesterol and other membrane lipids in AD has not been established, and it is not known whether and how such lipid alterations might lead to neuronal dysfunction and death.…”
mentioning
confidence: 99%
“…The analysis of temporal cortex from AD subjects showed loss of lipid rafts (MolanderMelin et al 2005), while hippocampi showed reduced cholesterol content in the rafts (Ledesma et al 2003). In addition the inhibition of cholesterol transport alters PS1 localization and APP processing in neuronal cells (Runz et al 2002).…”
Section: Human Conditions With Altered Cholesterol Biosynthesis: Consmentioning
confidence: 99%